Economic, Technological, and Environmental Feasibility of Green Hydrogen Adoption in Transportation: A Techno-Economic and Life Cycle Assessment Approach in Indonesia - Silfia; Khitara Aldilla Chandra; Ayu Putri Ana; M Reza Alfikri (Jurnal Penelitian Pendidikan IPA, 2025)
This research comprehensively evaluates the economic, technological, and environmental feasibility of green hydrogen adoption in Bogor City's transportation sector. Utilizing Techno-Economic Assessments (TEA), Life Cycle Assessment (LCA), and Scenario Modeling, the study compares centralized versus decentralized production pathways. TEA findings indicate that decentralized production is not financially viable, while centralized production with CCS technology shows positive financial potential, underscoring the role of economies of scale. LCA results confirm that green hydrogen offers significant emission reduction potential, up to 90% compared to fossil fuel alternatives, and produces zero emissions at the point of use, though high CCS costs remain a constraint. Scenario Modeling determined that Scenario 3 (high carbon tax, government subsidies, and reduced renewable energy prices) is the most effective pathway for accelerated adoption. Cost-Benefit Analysis (CBA) suggests that long-term non-economic benefits, such as improved public health and reduced air pollution, significantly outweigh high initial infrastructure costs. This study provides a novel, integrated assessment for a high-density urban context, advising policymakers to implement a higher carbon tax and subsidies to expedite the transition.